CULTURAL AND EDUCATIONAL LIBRARY WORK KNUKiM - Tolochko, Svetlana Ye. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Importance of cultural-educational and upbringing activities of university libraries for upbringing of the student youth is highlighted.